The influence of surface topology on the accuracy of laser triangulation scanning results - Vukašinović, Nikola (Strojniški vestnik, 2010)
This paper discusses the influence of surface topology on the accuracy of laser triangulation scanning results. Scanning distance and scanning angle of impact laser beam was found to be the most crucial interaction between the surface topology and scanning process. Therefore, we focused these two parameters while other parameters like microstructure, colour of surface, optical settings remained fixed. Despite of random nature of freeform surfaces, the measurements were systematic, according to the principles of thedesign of experiment (DOE) adjusting angle and distance in the whole scanning range. Based on the results of this research and prior estimation of surface complexity, an implication or working area range prediction, as well as the determination of optimal set of influence parameters inside this particular working area can be done.
Keywords: laserska triangulacija; laserski merilniki; površine; topologija; vzvratno inženirstvo